ANALISIS SEBAGIAN SEKUEN DNA DARI GEN MEISA1 PADA UBI KAYU (Manihot esculenta Crantz.) GENOTIPE MENGGALO DAN ROTI - Dewi Indriyani Roslim; Shinta Oktavia (DINAMIKA PERTANIAN, 2015)
Starch metabolism involves isoamylase1 enzyme and the gene encoding of this enzyme in cassava (Manihot esculenta Crantz.) is called meisa1 gene. The study aimed to analyze partial DNA sequences of meisa1 gene on menggalo (as bitter genotype) and roti (as sweet genotype) cassavas. Cassavas were grown in the garden at Department of Biology, Riau University in March to June 2014 with a code MG1, MG2, and MG3 for menggalo and Ry1, Ry2, Ry3 for bread. Research methods included DNA extraction, electrophoresis, PCR, sequencing, and data analysis. Data were analyzed using BLAST (Basic Local Alignment Search Tools) and MEGA (Molecular Evolutionary Genetics Analysis) program version 6:06. The results showed that there were few substitution mutations in the partial DNA sequence of meisa1 gene on cassava menggalo and roti cassavas and those mutation occured frequently in intron regions. Menggalo and roti cassavas had more Adenin (A), i.e. 34.7% and 35.2%, respectively. The ratio of (A + T) / (G + C) for the sixth cassava plants is almost the same ranging from 1.67 to 1.78. Genetic distance between the two genotypes of cassava based partial DNA sequences of meisa1 gene ranged from 0.11 to 0.21.